The Structure and Use of Mosques in Indonesian Islam: The Case of Medan, North Sumatra - Federspiel, Howard M. (Studia Islamika, 1996)
The mosque has an important position in Islam and Muslim lives. Prophet Muhammad, especially after the migration to Medina, to build a mosque as a center of worship and social activities of Muslims. This paper examines the existence, role and use of mosques in Indonesia, with a case study in Medan, capital of North Sumatra province. Through studies on these aspects, can be seen standing mosque in the contemporary period.DOI: 10.15408/sdi.v3i3.800